COMPARISON OF TOTAL FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY OF PURPLE LEAF EXTRACT (Graptophyllum pictum (L.) Griff.) USING MACERATION AND SOXHLETATION EXTRACTION METHODS - Darotulmutmainnah, Azmi; Marini, Marini; Herliningsih, Herlingsih; Handayani, Hana (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Purple leaves in Indonesia can be used as an anti-inflammatory medication and laxative to treat hemorrhoids, rheumatism, boils, and skin diseases. Purple leaves are also used as free-radical antidotes. This was due to the presence of secondary metabolite compounds in purple leaves. The right extraction method determines the amount of flavonoids that can be extracted and achieves a high flavonoid content. This study aimed to determine the total flavonoid content and antioxidant activity of purple leaves using different extraction methods, namely maceration and Soxhletation. This study employed an experimental method of testing total flavonoid levels using UV-Vis spectrophotometry and antioxidant activity using the DPPH method. The results showed that the maceration method yielded a total flavonoid level of 4,422 ± 0,047 ppm, which was higher than that obtained using the Soxhletation method (1,547 ± 0,027 ppm). In the antioxidant activity test, vitamin C was used as a comparator, with an IC50 of 2.263 ppm (very strong). The IC50 of purple leaf extract using the maceration method was 123,32 ppm (medium), while the soxhletation method yielded an IC50 of 104,42 ppm (medium). This shows that vitamin C has more potent antioxidant activity in counteracting free radicals than purple leaf extract, using maceration and Soxhletation methods. The results showed a significant difference in total flavonoid levels using different extraction methods, while there was no significant difference in the antioxidant activity of purple leaf extract using maceration and Soxhletation methods. Keywords: antioxidant, extraction, flavonoid, maceration, purple leaf, soxhletation